Nutrient concentration in leaves, a tool for nutritional diagnosis in cocoa. - Puentes-Páramo, Yina Jazbleidi (2016)
The aim of this study was to estimate the foliar concentrations in cocoa farming (Theobroma cacao L) as a diagnostic tool of their nutritional status. At the Research Center of the National Federation of Cocoa Producers (Fedecacao) located in Miranda-Cauca, Colombia, the study assessed the effect of five doses of NPK fertilization in nutrient concentration in leaves of four cocoa clones CCN-51, TSH-565, ICS-39, and ICS-95 from 20102012. Experimental design was randomized complete block design with five treatments: TR(control), T1(25% NPK), T2(50% NPK), T3(75% NPK), T4(100% NPK) and four replicates. The concentration of 11 nutrients (N, P, K+, Ca2+, S, Mg2+, B, Zn2+, Cu2+, Fe2+, Mn2+) and their relation with yield was evaluated for three years. Results showed differences in the foliar concentration of nutrients assessed by effect of treatments, by clone, and by clone*treatment interaction. The foliar concentration used was derived from higher yield-related treatment, whereby, a proposal for nutritional diagnosis in cocoa based on nutrient monitoring was created to evaluate nutrient concentration in leaves.